La Organización Familiar en el Rendimiento Académico en los niños de tercer año de Educación Básica paralelo “B”, de la Unidad Educativa José María Román ubicada en la provincia de Chimborazo, Cantón Riobamba, año lectivo 2015 – 2016. - Lema Avalos, Paola Lucía (2016)
This research aims to determine the impact of the Family Organization on Academic Performance in the third year of Basic Education "B". The theoretical framework establishes concepts such as: Family organization, models, roles, academic performance, types, other factors and the methodological method was used the inductive method as part of singular premises to arrive at general conclusions, the deductive of general facts to arrive at particular conclusions, the design of the research is non-experimental because it does not the variables were manipulated, the type of research was field because it was carried out in the place of the facts directly with the involved ones, and descriptive theoretical because allowed to know the characteristics, to describe situations, phenomena, the population was 40 students and 40 representatives from the third parallel year "B" for which it was not necessary to extract samples, the technique applied was the survey, the instrument questionnaire, which allowed information to be obtained from which the analysis and interpretation, where it was identified that the majority of students live in a nuclear model organization.